Between modernity and prudence: the transposition into French law of Directive (EU) 2019/1023 of 20 June 2019 on restructuring and insolvency - Mastrullo, Thomas (European Insolvency and Restructuring Journal, 2023)
Ordinance n° 2021-1093 of 15 September 2021, which came into force on 1 October 2021, transposed into French law Directive (EU) 2019/1023 of 20 June 2019 on restructuring and insolvency. This transposition, prudent and respectful of the terms of the Directive, modernizes French insolvency law without overturning it. The most notable advances concern the adoption of restructuring plans, with the introduction of classes of affected parties and the mechanism of cross-class cram-down, as well as the institution of a new sauvegarde accélérée preventive procedure. More generally, several advancements are to be welcomed in terms of prevention, negotiation of restructuring plans, second chance of entrepreneurs and efficiency of procedures.